2014
DOI: 10.22146/bpsi.11452
|View full text |Cite
|
Sign up to set email alerts
|

Program Manajemen Stres Kerja di Perusahaan: sebuah Petunjuk untuk Menerapkannya

Abstract: Job stress is an iceberg phenomen. A great number of unreported cases and there is no aplicative program in Keywords: stress management programs, job performance, company image1 Stres kerja (job stress) merupakan sebuah fenomena gunung es. Banyaknya kasus-kasus yang tidak terlaporkan dan berisiko makin meluasnya masalah stres kerja dengan segala dampak negatifnya di masyarakat. Tuntutan beban tugas yang semakin kompleks disertai relationship yang tidak harmonis di tempat kerja merupakan sumber utama timbulnya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…This research is synergized with other researchers such as (a) Sutrisno ( 2010) revealed that the contribution of organizational culture, work stress, and commitment to employee performance is 83.50%; (b) Purnawati (2014) explained that an ideal work stress management program includes primary, secondary, and tertiary prevention refers to the workers and employer's need; (c) Noor, et al (2016) explained that workers must be free from stressful conditions because job stress and job satisfaction have a simultaneous and significant effect on employee performance; (d) Susetyo & Ratnaningsih (2016) explained that the perception of K3 had an effective effect of 13.6% on the work stress of production employees; (e) Wartono (2017) explained that job stress affects magazine employee performance by 77.44%.…”
Section: Resultssupporting
confidence: 67%
“…This research is synergized with other researchers such as (a) Sutrisno ( 2010) revealed that the contribution of organizational culture, work stress, and commitment to employee performance is 83.50%; (b) Purnawati (2014) explained that an ideal work stress management program includes primary, secondary, and tertiary prevention refers to the workers and employer's need; (c) Noor, et al (2016) explained that workers must be free from stressful conditions because job stress and job satisfaction have a simultaneous and significant effect on employee performance; (d) Susetyo & Ratnaningsih (2016) explained that the perception of K3 had an effective effect of 13.6% on the work stress of production employees; (e) Wartono (2017) explained that job stress affects magazine employee performance by 77.44%.…”
Section: Resultssupporting
confidence: 67%
“…Psychological distress was measured using a questionnaire containing 18-item statements with 4 Likert’s scale that were quoted from the BJSQ questionnaire 16 in the Indonesian version. 17 The author had permission to use BJSQ from Professor Norito Kawakami (who also developed a New Version of BJSQ 18 with Akiomi Inoue et al) during a short-term study at Tokyo University, Japan. The questionnaire contains the following statements: Very active; Full of energy; Very lively; Feel angry; Inwardly annoyed/aggravated; Irritable; Extremely tired; Exhausted; Weary/listless; Tense; Worried/insecure; Restless; Depressed; Doing anything is a hassle; Unable to concentrate; Feel gloomy; Unable to handle work, and Feel sad.…”
Section: Methodsmentioning
confidence: 99%
“…Work stress is the response people may have when presented with work demands and pressures that are not matched to their knowledge and abilities and which challenge their ability to cope (WHO, 2020b;Vanchapo, 2020). The demands of an increasingly complex workload accompanied by disharmonious relationships in the workplace are a major source of stress on employees (Purnawati, 2014). Demands, burdens, work colleagues, and the results of work stress can influence verbal abuse behavior, including scolding, yelling, cursing, blaming, insulting, threatening, mocking, degrading, criticizing, and underestimating children.…”
Section: Relationship Between Mother's Work Stress Level and Verbal Abuse Behavior Among School-age Childrenmentioning
confidence: 99%